Fe3O4 nanofluid injected photonic crystal fiber for magnetic field sensing applications - Mitu, Sumaiya Akhtar; Dey, Dipak Kumar; Ahmed, Kawsar; Paul, Bikash Kumar; Luo, Yanhua; Zakaria, Rozalina; Dhasarathan, Vigneswaran (Elsevier, 2020)
This work proposes a novel magnetic field sensor based on nanoparticle ferrosoferric oxide (Fe3O4) magnetic fluid for different magnetic field strength from 100 Oe to 160 Oe. Investigations are performed to verify the simulation model and measure the spectral shift for applied magnetic field strength. The results of this task indicate that it has high sensitivity response with the variation of various magnetic field strength (Oe). The reported sensitivity as 83268.46 nm/RIU and 83188.25 nm/RIU for both for X and Y polarization respectively and it will be the maximum sensitivity to the best of knowledge. The other significant of this work that the proposed sensor seem to be as simple structure, low cost, high accuracy and also helpful for microfluidics technology. © 2019 Elsevier B.V.